Everything you need to know about teen marriage - Ayer, Eleanor H. frey50 (Rosen Pub. Group New York, 1990)
Examines the choices involved in teenage marriage, as well as the joys, problems, and implications. presents case studies for and against teenage marriage
Keywords: Teen Marriage -- United States -- Relationships